Association of advance care planning with hospital use and costs at the end of life: a population-based retrospective cohort study - Ian Scott; Liz Reymond; Xanthe Sansome; Hannah Carter (BMJ Open)
Objective To investigate associations between the availability and timing of digitally available advance care planning (ACP) documents and hospital use and costs during the last 6 months of life.Design Retrospective population-based cohort study using data linkage.Setting 11 public hospitals in Queensland, Australia.Participants 5586 decedents with ACP documents were directly matched 1:2 to 11 172 control decedents based on age category, sex, location, year of death and principal diagnosis code for the last-known hospital admission.Exposure ACP discussions with documents uploaded to a widely accessible statewide digital platform. Directly matched subgroup analyses investigated differences between decedents with ACP documents available at three different times prior to death: ≥6 months, between 1 and 6 months, and <1 month.Main outcomes and measures Emergency department (ED) presentations, hospital and intensive care unit (ICU) admissions, and in-hospital deaths, expressed as adjusted OR (aOR). Secondary outcomes were hospital bed-days and costs.Results ACP decedents with documents uploaded ≥6 months prior to death, compared with controls, had fewer ED presentations (aOR 0.90, 95% CI 0.81 to 1.00), hospitalisations (aOR 0.83, 95% CI 0.74 to 0.92), ICU admissions (aOR 0.23, 95% CI 0.10 to 0.48), and in-hospital deaths (aOR 0.56, 95% CI 0.51 to 0.63), and lower adjusted mean hospital costs per person over the last 6 months of life ($A2290 less (95% CI −$4116 to −$463)). Conversely, decedents with ACP documents uploaded less than 6 months prior to death showed higher rates of ED presentations and hospital admissions and greater hospital costs relative to controls.Conclusion The association between digitally available ACP documents and health service use and cost differed based on the timing of ACP upload, with documents available ≥6 months prior to death being associated with less hospital use and costs.